RECENT TRENDS IN MALE REPRODUCTIVE HEALTH PROBLEMS - Sengupta, Pallav (Asian Journal of Pharmaceutical and Clinical Research, 2014)
This review critically evaluates the current trends of male reproductive health problems in relation to semen quality. Increasing trend in male reproductive disorders observed in recent years, are principally found to associate with lifestyle and environmental factors. Lifestyle-allied diseases could be controlled with modification in diet, living and working environment etc. This review outlines the changing trends in male reproductive health and highlights the alterations in semen quality, in scientific manner. Though scientific and public concern regarding the changes on male reproductive health has grown in past few decades but the demonstration of a geographical differences in sperm concentration, still appears to be controversial. The amplitude of the difference observed cannot only be explained by methodological or confounding factors, and must to some extent be attributed to ethnic, genetic or environmental factors. However, there are numerous reports indicating the chronologically declining sperm count and standard semen parameters in various population indicating the increasing trend of male reproductive health disorders.